Analisis dan Perencanaan Perbaikan Papan Petunjuk Arah Pada Wisata Candi Jiwa Batujaya Karawang - Moch Kahfi Ariansyah; Wahyudin; Kusnadi; Dene Herwanto (Jurnal Serambi Engineering, 2024)
The Maps and Directions screen is an example of a screen that provides information about the place you are going to. This display shows a sequence of commands such as turn left, go straight, and so on. Depending on its function, the directional display is very useful in providing information to its users (such as drivers and pedestrians) to reduce errors in reading or understanding. The directional sign to the tourist location of Jiwa Temple site is still not ergonomic because many of the directional signs are broken, use dark colours, are not placed properly, there are letters on the directional sign that have faded, and there are even roads that do not have directional signs at the intersections of the road to the tourist location of Jiwa Temple Batujaya site, making it difficult for tourists to visit Jiwa Temple Batujaya, so it does not meet the requirements or criteria for a good sign, namely visibility, legibility and readability. Therefore, it is necessary to improve the directional sign so that it can reduce the discomfort of the community or tourists in visiting the cultural heritage site of Jiwa Temple Batujaya Karawang.